2023
DOI: 10.1039/d3fo01550e
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake patterns during pregnancy and excessive gestational weight gain: a systematic review and meta-analysis

Abstract: Excessive gestational weight gain (EGWG) is associated with gestational complications and adverse birth outcomes. Dietary intake is closely related to EGWG; however, evidence on the association between different dietary patterns...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The pregnant persons’ dietary habits, including adequate dietary intake (e.g., sufficient kilocalorie and macronutrient intake) and dietary quality (e.g., high fruit and vegetable intake) during pregnancy have been shown to positively impact GWG [ 11 , 39 ]. A 2023 systematic review and meta-analysis from fourteen studies across eleven countries (n = 77,550) found that unhealthy dietary patterns, consisting of greater saturated fats and simple carbohydrates, were associated with an increased odds of experiencing excess GWG (OR = 1.22, 95% CI: 1.02–1.45, p = 0.031), regardless of their pre-/early pregnancy BMI [ 40 ]. Therefore, improving diet habits and eating behaviors may act as a strategy for enhancing opportunities to achieve the recommended GWG.…”
Section: Discussionmentioning
confidence: 99%
“…The pregnant persons’ dietary habits, including adequate dietary intake (e.g., sufficient kilocalorie and macronutrient intake) and dietary quality (e.g., high fruit and vegetable intake) during pregnancy have been shown to positively impact GWG [ 11 , 39 ]. A 2023 systematic review and meta-analysis from fourteen studies across eleven countries (n = 77,550) found that unhealthy dietary patterns, consisting of greater saturated fats and simple carbohydrates, were associated with an increased odds of experiencing excess GWG (OR = 1.22, 95% CI: 1.02–1.45, p = 0.031), regardless of their pre-/early pregnancy BMI [ 40 ]. Therefore, improving diet habits and eating behaviors may act as a strategy for enhancing opportunities to achieve the recommended GWG.…”
Section: Discussionmentioning
confidence: 99%
“…These cravings may be linked to the brain's response to stress hormones [44,[46][47][48][49]. Stress triggers the release of hormones, such as cortisol, which can impact metabolism and lead to weight gain, especially around the abdominal area.…”
Section: How Stress Influences Diet and Dietary Behavior In Womenmentioning
confidence: 99%